A concrete psychological investigation of ifá divination/ una investigación psicológica concreta de la adivinación de ifá/ uma pesquisa psicológica concreta da adivinhação de ifá (2012)
Divination -the consultation of an oracle in order to determine a course for future action- has long been considered a practice characteristic of "primitive mentality." We describe research with the babalawo of Santería, who are expert in the divinatory system of Ifá. Our first goal is to offer an example of what Vygotsky called "concrete psychology": the study of particular systems of psychological functions in the concrete circumstances of specific professional complexes. Our second goal is to explore the character of divination as psychological and social process, given the somewhat negative views of divination expressed by many social scientists, including Lévy-Bruhl and Vygotsky himself. Analysis of a recorded consultation identified features characteristic of institutional discourse. We argue that the institutional facts of divination may constitute an unfamiliar ontology, but the epistemology -the appeal to logic and to empirical evidence- is a familiar one.